Bitumen Modification Using Buton Natural Rock Asphalt - Ayu Fitrianti; Rizal Palefi Hidayat; Gatot Rusbintardjo; Abdul Rochim (International Conference on Coastal and Delta Areas, 2017)
In Buton Island, an island located in South-East Sulawesi Island in Indonesia is found about 700 million tons natural rock asphalt (NRA) which have not been maximally utilized yet. Buton-NRA contains 20 to 30% of bitumen. This paper reported the experimental study on utilizing of Buton-NRA as additive of bitumen binder in hot mix asphalt (HMA) mixtures. Amount of 5, 10, 15, 20, 25% of very fine of Buton-NRA was added into the bitumen, resulted Buton-NRA-Bitumen’s binder. Penetration and softening point test were conducted to get penetration index (PI) value, an index to determine the temperature susceptibility of the binder. The results show that the Buton-NRA-Bitumen’s binder has low temperature susceptibility. Used as binder in HMA mixtures also shown that the Buton-NRA-Bitumen’s binder can improve the performance of the mixtures. Marshall Stability and stiffness of the mixtures are higher compared to that of base bitumen binder, especially Buton-NRA-Bitumen’s binder with 15% of Buton-NRA, Marshall Stability reaches 1620kg and stiffness 142kg/mm, while HMA mixtures with base bitumen (0% Buton-NRA) only has 1068kg of Marshall stability and 110kg/mm of stiffness. Keywords: Buton-Natural Rock Asphalt, Binder, Improve, Performance, HMA mixtures.